Standardvariation. Wie viel Variation verträgt die deutsche Sprache? - Eichinger, Ludwig (Jahrbuch des Instituts für Deutsche Sprache, 2005)
The papers in this volume focus on the following questions: what does the term 'standard language' comprise, how has Standard German developed since the 19th century, how can linguistics adequately describe its present state, and what longerterm developmental tendencies can be identified in it? The answers to these questions also reflect the necessity for normativity and its boundaries.